Students' Critical Thinking Skills Through Active Learning - Riska Nur Magfira Rusdi; Wahyullah Alannasir; Erik Setiawan; Nur Fadilah; Andi Amanda Nur Istiqomah; Dwi Alfitri Nabila (International Journal of Technology and Education Research, 2026)
Critical thinking skills are essential competencies that elementary school students must possess to meet the challenges of 21st-century learning. This study aims to analyze the role and effectiveness of active learning in enhancing students' critical thinking skills. The method used is a literature review analyzing relevant studies published in accredited scientific journals from 2020 to 2025. The results of the review indicate that active learning approaches, such as problem-based learning, inquiry-based learning, discovery learning, and STEAM-based approaches, have been proven to significantly enhance students' critical thinking skills. This improvement is influenced by students' active engagement in the learning process, their prior knowledge, and the learning environment's support. Additionally, both internal and external factors contribute to the development of critical thinking skills. Active learning provides students with the opportunity to analyze, evaluate, and solve problems independently and collaboratively. Thus, it can be concluded that active learning is an effective and relevant strategy for implementation in elementary education to optimally develop students' critical thinking skills.